Twarz i (jej) brak. O filmie Lokator Alfreda Hitchcocka - Tomczyk-Jarzyna, Izabela (Załącznik Kulturoznawczy, 2020)
The article concentrates on the way in which face is presented in the first ‘Hitchcock Picture’ – The Lodger movie. In this text, face is understood as a set of elements that determine identity, but also have the potential for changes. Starting from the drawing of an unsuccessful shot from the movie and referring to its full title (The Lodger – A Story of the London Fog), the author focuses not only on face, but also on the role of fog in presenting the face of the city and constructing the face of the title character. Alfred Hitchcock’s decisions concerning the manner of presenting face are analyzed in the context of Béla Balázs theory and German film expressionism.